Analysis of Bacterial Community Composition and Ecological Function during Soft Rot Process in Pitaya (Hylocereus spp.) Stems. (6th May 2022) - Peng, Zhijun; Guan, Jingqiang; Mou, Dan; Zou, Xiao; Wang, Bin; Jin, Jilin; Zhang, Xingwu; Luo, Hui
Abstract : The soft rot in pitaya ( Hylocereus spp.) stems seriously affected the harvest of pitaya fruits, but the dynamic change characteristics of bacterial community in pitaya stems during soft rot stages had not been revealed. In this study, we analyzed the bacterial community composition of different soft rot stages and visualized functional annotations of the core bacterial community in five soft rot periods via the Illumina high-throughput sequencing technology, MetaCoMET online network platform, and FAPROTAX database. The results showed that the dominant bacteria in healthy and diseased pitaya stems were Proteobacteria and Firmicutes. Pseudomonas, Enterobacter, Sphingomonas, and Sphingobacterium were the core bacteria microbiomes during the infection stages. Meanwhile, the ecological function analysis results showed that the Enterobacter and Pseudomonas bacteria may play an important role in causing soft rot of pitaya stems. Therefore, the results shown in this paper could provide a useful reference for the study on microecological mechanism of soft rot of pitaya stems.